Ontological model of virtual community of practice (VCoP) participation : a case of research group community in higher learning institution - Abdul Razak, Siti Hajar; Eri, Zeti Darleena; Abdullah, Rusli; Azmi Murad, Masrah Azrifah (Indian Society for Education and Environment, 2013)
The increasing number of Virtual Communities of Practice (VCoP) leads to the needs of having an ontological model in mapping new members (new researchers) to their relevant Research Group(s) especially in Higher Learning Institution. This paper proposes a new model of ontology of Virtual Community of Practice (VCoP) called Ontology-based VCoP (Onto-VCoP) that can help new member of researcher to identify themselves for the suitability of joining research groups efficiently. The efficiency of our model is based on mapping technique that was adopted from Ehrig and Staab [1] Quick Ontology Mapping (QOM). Onto-VCoP model applied ontology to represent knowledge and QOM to map data between new researchers and research groups. Systematically reviewed for literature and pre-survey is done to get the user requirement and to support objective of this paper. The result shows Onto-VCoP model may help new researchers to identify research groups based on their research interest efficiently.